Qualidade de vida na pós-graduação stricto sensu no contexto do produtivismo acadêmico. - Audibert, Simone de Almeida (2019)
Graduate education in Brazil is historically recent. Since the 80's, it went through a expressive expansion, experiencing changes that affected the evaluation system and prioritized the scientific production and, consequently, the research. These changes have brought positive and negative results to the quality of graduate programs and the quality of academic life and science. Currently, quantitative metrics have become the main indicator in the scientific production, with consequences for teaching and researcher training. According to the literature, scientific development comes at the expense of significant psychological and emotional distress among actors involved. This study aimed to investigate the graduate students’ perception about their quality of life in their academic and life experiences. The results showed low indices of general quality of life; low levels of quality of graduate life in terms of physical and psychological aspects, and better assessments of personal and professional factors; and worrying scores of anxiety, depression and stress, with 30% of graduate students at severe and very severe levels. It can be realized that women, masters and scholars constitute a risk group and should be focus of quality of life and health promotion programs. These statistics corroborate the literature revewed and allow the understanding of this question as a collective phenomenon, holding off from individual diagnoses. Therefore, this study points out the need to seek ways of coping that privilege the collective field, besides promoting spaces for dialogue and critical reflection. It also suggests strategies in way to consider the most impact factors in graduates’ quality of life and health, such as: assurance of necessary time for leisure, social life, rest and sleep; adequate financial resources; positive experiences regarding orientation process and relationship with teachers; activity load balance; and promotion of activities to strengthen graduate students’ relationships.